Guided Inquiry Learning Model Integrated with Peer Instruction: Its Impact on Grade Xi Students' Critical Thinking Skills in Thermochemistry - Nisa, Khairatun; Copriady, Jimmi; Haryati, Sri (Universitas Pendidikan Mandalika, 2026)
This study examines the effectiveness of a guided inquiry learning model integrated with peer instruction in improving students’ critical thinking skills. An experimental method employing a randomized control group pretest–posttest design was implemented in two Grade XI MIPA classes at SMAN 2 Tambang. The research instruments consisted of pretest and posttest assessments comprising 25 items developed based on 11 indicators of critical thinking skills. Data were analyzed using inferential statistics. Prior to hypothesis testing, assumptions of normality and homogeneity were examined using the Liliefors and Levene’s tests, respectively. Hypothesis testing was conducted using an independent samples t-test to determine differences in critical thinking skills between the experimental group, which received guided inquiry instruction integrated with peer instruction, and the control group, which was taught using a conventional guided inquiry learning model. The significance level was set at α = 0.05. The results indicate that the mean gain in critical thinking skills in the experimental group (54.58) was higher than that of the control group (48.98). The hypothesis testing yielded a t-value of 10.56, exceeding the critical t-value of 1.987 at the 0.05 significance level, indicating a statistically significant difference between the two groups. These findings demonstrate that the guided inquiry learning model integrated with peer instruction is effective in enhancing students’ critical thinking skills in thermochemistry. Therefore, this model is recommended for chemistry teachers to improve student engagement and foster higher-order thinking skills in chemistry learning.